Peran Anggota Keluarga dalam Meningkatkan Prestasi Belajar Pendidikan Agama Katolik Siswa-siswi Kelas II SD Joannes Bosco Yogyakarta - Agnes Sri Antari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The aim of this study is to evaluate the effectiveness of the learning process. Based on observations of teacher activities during Cycle I, teacher engagement increased from 65% in the first meeting to 81% in the second meeting. This improvement indicates that teacher activity falls within the